2013
DOI: 10.3324/haematol.2013.086066
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lymphocytic leukemia in young (<= 55 years) patients: a comprehensive analysis of prognostic factors and outcomes

Abstract: ABSTRACTto evaluate the experience of CLL patients who were ≤55 years of age at the time of diagnosis. The threshold of ≤55 years was selected to classify age based on a similar cutoff used to define young CLL patients in historical studies. 5,7,29,30 Patients diagnosed with CLL between January 1995 and April 2012 and who fulfilled the 1996 criteria for CLL 31 and/or the World Health Organization (WHO) criteria for small lymphocytic lymphoma 32 were included in this analysis. Rai stage was ascertained within 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
37
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 36 publications
(36 reference statements)
8
37
1
1
Order By: Relevance
“…In agreement with other reports, 16,21 elderly patients were treated less frequently than younger ones. There are various potential reasons for this, including less aggressive disease 21 and a more, not pre-determined conservative approach to the management of older subjects. Also, most elderly patients were given no effective therapies, which resulted in a lower overall response rate.…”
Section: Discussionsupporting
confidence: 82%
“…In agreement with other reports, 16,21 elderly patients were treated less frequently than younger ones. There are various potential reasons for this, including less aggressive disease 21 and a more, not pre-determined conservative approach to the management of older subjects. Also, most elderly patients were given no effective therapies, which resulted in a lower overall response rate.…”
Section: Discussionsupporting
confidence: 82%
“…Our knowledge of the clinical picture and behavior of CLL diagnosed at a young age does, however, come from studies conducted in the late 1980s 4,5 and 1990s, 6-9 a time when most biomarkers currently analyzed in CLL patients had not yet been discovered, [10][11][12][13] therapy was still based on alkylating agents, 14 and the role of allogeneic stem cell transplantation was not well established. 15 In this issue of Haematologica, Parikh et al 16 have reviewed the clinical and biological characteristics, and outcome of CLL patients diagnosed at ≤55 years of age. They compared the clinical and biological characteristics of 844 CLL patients ≤55 years, 55% of them with biomarkers available, with those of 2324 older patients followed-up at the Mayo Clinic from January 1995 to April 2012, and with the sex-and agematched general population.…”
mentioning
confidence: 99%
“…Parikh et al (24) divided 3168 patients into two groups as under and over 55 years age and found that 44% of patients younger than 55 years of age had stage 0, 53% had stage 1-2, 3% had stage 3-4 disease. 57% of patients over 55 years had stage 0, 37% had stage 1-2, and 6% had stage 2-4 disease.…”
Section: Discussionmentioning
confidence: 99%